Sosialisasi Peran Orang Tua dalam Melindungi dan Memenuhi Hak-Hak Anak - Wa salmi; Nur Hidayatin; Sugiono Sugiono; Umar Polimba; Desi Arunia Wati; Alimudin Alimudin (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Parents in an effort to create or shape good child behavior, of course, will be a responsibility and challenge in itself. Given that lately, there have been many cases of violence against children by their own parents, under the pretext of educating, there are also cases of parents who neglect their children for various reasons, this is certainly a serious concern. The purpose of this activity is to provide education to the community, especially parents, about their role in protecting and fulfilling children's rights. The method used is to provide counseling and simulations to parents. Related The results of this activity are able to provide a conceptual picture related to the protection and fulfillment of children's rights.